Land Use and Land Cover Change Detection of Ganakbari Mauja in Savar Upozila (Global Journal of Human-Social Science, 2016)
The aim of this work is to study the changes in land use in the study area in manner that can aid quick and useful decisions for the purpose of land development, administration and planning for a sustainable environment. The main objective of the study is to analyze the land use changes in Ganakbari Mouza. This study has used mainly primary and secondary data. Stratified random sampling was used for primary data, and secondary information (data) was collected from various secondary sources. Findings revealed that in liner pattern of growth which is taking in haphazard manner. Irresponsibility of RAJUK and other related development authority is the main cause of this haphazard growth. Lack of land use policy, zoning regulation and other controlling rules and laws are also responsible for this uncontrolled and unplanned development. But as a potential area of development, Ganakbari may play an important role in whole region. It may also the role of an efficient and suitable satellite city for the megacity Dhaka. It is concluded that remote sensing and GIS tools provide an outstanding platform from which accurate information on Land use changes and patterns can be obtained and that Ganakbari area of Dhamsona union has experienced tremendous changes in land use, so efforts should be made to regularly update available data in order to control further development.
Keywords: land cover change; ganakbari mouja; land use